Idris Sardi’s Influence on Musical Development and Education in Indonesia - Fu'adi, Fu'adi; Sudira, Putu; Astuti, Kun Setyaning (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
Idris Sardi is known as a music maestro in Indonesia. This study aims to reveal the influence of Idris Sardi on the development of music and its implications in music education. This study uses a qualitative method with a narrative approach. The data were collected through observation, in-depth interviews, and documentation. The research informants were carefully selected from the family, violin students, and colleagues of Idris Sardi in Jakarta and Bogor, West Java. The data were analyzed by organizing data and creating codes, describing codes in chronological categories and themes, developing interpretations, and visualizing data. The results showed that Idris Sardi was influential in developing (1) keroncong music by varying the tempo and expanding the repertoire; (2) the violin playing techniques included unique characters such as vibrato, glissando, and octave variations; (3) ethnic and popular music were made through orchestrations and collaboration with orchestral music. The implications in music vocational education were (1) problem-based learning by creating a new keroncong style to be accepted by society; (2) the improvement capability by exploring skills to play the violin; (3) life-based-learning by raising local and popular music to be qualified while enhancing the level of society’s music appreciation. In conclusion, Idris Sardi provided a strong influence on the music development in Indonesia, and the implication could be a new strategy to improve the quality of music education.